Biomarkers for assessment of Skeletal maturation - Singh Kahlon , Sukhdeep; Aggarwal , Vijay; Singh Ahluwalia, Karamdeep; Singh Narang, Ramandeep; Singh, Balwinder; Kahlon, Monaliza (International Journal of Psychosocial Rehabilitation, 2020)
While making orthodontic treatment plans, the most important objective is to correct skeletal discrepancies by utilising the growth potential of the patient so that the most favourable results could be achieved. Response to orthopaedic treatment modalities is maximum during the peak of adolescent growth spurt. The correct identification of the prepubertal and postpubertal growth phases on an individual basis is very important in orthodontic diagnosis and treatment planning. [2] Orthopaedic treatment of patients with Class III malocclusion and rapid maxillary expansion achieves maximum efficacy when performed at a pre-pubertal growth phase. On the other hand, in Class II subjects, the amount of supplementary mandibular growth induced by functional appliances appears to be significantly greater when the treatment is performed during the pubertal growth phase.